EVALUATING SERVICE QUALITY OF PUSKESMAS PINELENG USING IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Rompas, Angelic Solagratia (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT The development of globalization become a company motivation to give a good service to customer to get interest dan make customer satisy with the service. Public service is one of the government responsibilities to play a role important in providing health care to the public. Puskesmas is one of the health agencies to improve the quality of performance.The study aims to analyze the service quality of Puskesmas Pineleng using Importance Performance Analysis (IPA). 50 Puskesmas patients were surveyed as respondents. The result shows (1) Facilities and Hospitality are located in quadrant I, (2) Received complaint and Building Condition are located in quadrant II, (3) nurse duty is located in quadrant III and (4) Providing Information and Appropriate Procedure are located in quadrant IV. Puskesmas Pineleng should maintaining the good performance of service and enhancing the low performance of service to ensure the service quality better than before. Keywords: Service Quality, Importance-Performance Analysis, Puskesmas